2013
DOI: 10.1007/s12525-013-0123-9
|View full text |Cite
|
Sign up to set email alerts
|

New business client acquisition using social networking sites

Abstract: The rapid development and expansion of the social services and social networking sites (SNSs) on the Internet has boosted interdisciplinary research on online communities as a part of social network analysis. Social networking creates a unique opportunity to establish new business contacts with people from unexplored markets to gain new customers or contractors. The goal of the paper is to present a new idea for acquisition of new customers in the business-to-business market using individual human relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 20 publications
2
18
0
Order By: Relevance
“…These findings are consistent with previous research findings (e.g. Kietzmann et al, 2011;Ribiere and Tuggle, 2010;Kazienko et al, 2013;Constantinides et al, 2008;Jussila et al, 2014;Nord et al, 2018). Such about the firm, its products and about their own needs and preferences.…”
Section: Impact Of Social Media International Marketing On Internatiosupporting
confidence: 93%
See 2 more Smart Citations
“…These findings are consistent with previous research findings (e.g. Kietzmann et al, 2011;Ribiere and Tuggle, 2010;Kazienko et al, 2013;Constantinides et al, 2008;Jussila et al, 2014;Nord et al, 2018). Such about the firm, its products and about their own needs and preferences.…”
Section: Impact Of Social Media International Marketing On Internatiosupporting
confidence: 93%
“…Examples of these benefits are that they make it possible to share tacit knowledge and facilitate the acquisition of knowledge (Ribiere and Tuggle, 2010). In order to achieve business success, the social media can be used not only to deliver information to customers but also to gather information about clients and potential markets (Kazienko et al, 2013). A considerable body of research exists on the high quality of useful information that can be obtained by monitoring social media platforms for marketing purposes, i.e.…”
Section: The Effect Of Social Media Use On Understanding Customers' Vmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior research on electronic markets has shown that incorporating personal data into electronic market mechanisms is very useful -for example for customer acquisition (Kazienko et al 2013) or better pricing (Rayna et al 2015). The conceptional framework by Ngai et al (2015a) opens the way to develop social network applications for electronic markets based on a user's personality as a well established theoretical basis for assessing consumer behavior.…”
Section: Personality and Consumer Behavior In (Electronic) Marketsmentioning
confidence: 99%
“…Finally the relevance of expertise ranking in social networks and Internet has been presented in some works to understand and exploit enterprise know-how [45], find competence gaps and learning needs inside corporations [46], improve Scrum processes [47], improve human to human interactions [48], or tackling information asymmetries in electronic marketplaces [49] to name a few.…”
Section: State Of the Artmentioning
confidence: 99%